Analisis Media Sosial Sebagai Sarana Komunikasi Bisnis Bagi Online Shop di Daerah Bandung - Zenn Virgiawan; Muhammad Imam Faizal; Ricky Firmansayah; Aliya Devi Ramadyta (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
Today, social media is no longer just a means of exchanging messages, but can be a source of income. Knowledge of social media, is the main foundation for running an online shop. The method used is the technique of collecting data through questionnaires distributed via Gform to respondents, then collecting data related to topics and related problems. Data analysis is done by reading, studying, studying, comparing and interpreting the results of the analysis, so that it can answer all the problems. The last stage is to draw conclusions from the problems that have been answered.Instagram is a social media that is almost owned by young people. Most of the reasons for selling their goods or services on Instagram are because there are more Instagram users in Bandung, including Whatsapp. Most consumers claim to use Instagram as a medium for shopping (62%), while WhatsApp ranks second (9%), followed by Facebook, TikTok, and others. Both in the eyes of sellers and consumers, both answered that communication in business is very important. As many as 82% of consumers decide to ask first about the product they are going to buy rather than buying directly like some other consumers (18%).